Diagnostic Accuracy of Ultrasound-Determined Amniotic Fluid Index Versus Measured Amniotic Fluid Volume at Caesarean Delivery and Its Impact on Perinatal Outcomes - Shaherzad Sohail; Faiza Iqbal; Sanya Imran; Rabia Mushtaq; Omar Altaf (Journal of University College of Medicine and Dentistry)
Objective: To assess the reliability of ultrasound-based amniotic fluid index (AFI) in estimating amniotic fluid volume by comparing it with intraoperative findings during caesarean section, and to evaluate its association with neonatal clinical outcomes in low-risk term pregnancies.